2020
DOI: 10.1051/0004-6361/201935791
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the formation pathways of formamide

Abstract: Context. As a building block for amino acids, formamide (NH 2 CHO) is an important molecule in astrobiology and astrochemistry, but its formation path in the interstellar medium is not understood well. Aims. We aim to find empirical evidence to support the chemical relationships of formamide to HNCO and H 2 CO. Methods. We examine high angular resolution (∼ 0.2 ) Atacama Large Millimeter/submillimeter Array (ALMA) maps of six sources in three high-mass star-forming regions and compare the spatial extent, integ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Mendoza et al (2014) and López-Sepulcre et al ( 2015) reported a correlation between the abundance of NH 2 CHO and HNCO based on their survey observations toward various star-forming regions from low-mass to high-mass ones. The abundance relationship was also reported with the ALMA observations (Coutens et al 2016;Allen et al 2020) and was supported by theoretical calculation (Quénard et al 2018). These works suggest some chemical relations between the two species.…”
Section: Nh 2 Chosupporting
confidence: 80%
“…Mendoza et al (2014) and López-Sepulcre et al ( 2015) reported a correlation between the abundance of NH 2 CHO and HNCO based on their survey observations toward various star-forming regions from low-mass to high-mass ones. The abundance relationship was also reported with the ALMA observations (Coutens et al 2016;Allen et al 2020) and was supported by theoretical calculation (Quénard et al 2018). These works suggest some chemical relations between the two species.…”
Section: Nh 2 Chosupporting
confidence: 80%
“…Single dish observations, which found a constant abundance HNCO/NH 2 CHO ratio in a range of source luminosities and masses (Bisschop et al 2007;López-Sepulcre et al 2015), suggested that these molecules were chemically-related. Evidence of co-spatial emission in the low-mass protobinary system IRAS 16293 (Coutens et al 2016), two high-mass cores in G35.20 (Allen et al 2017), and six cores across three massive star-forming regions (Allen et al 2020) further indicated a link between the two species.…”
Section: Hnco and Nh2chomentioning
confidence: 99%
“…Trot values in italics are those adopted from similar species, as described in the text. Column density upper limits are derived using 3σ line intensity upper limits and by assuming the median line FWHM from a chemically-related or observationally-linked species (e.g., CH3CH2CN/CH2CHCN, HNCO/NH2CHO; Caselli et al 1993;Allen et al 2020) the same. CH 3 OCH 3 , despite its unique column density distribution, remains strongly correlated with CH 3 OH irrespective of the inclusion or exclusion of HC1.…”
Section: 047mentioning
confidence: 99%
“…cosmic diatomic molecule, to deoxyribonucleic acid (DNA), which can have order of 10 8 carbon atoms, the search and detection of organic molecules in space contribute to our understanding of the emergence of life. Research on molecules such as HNCO, H 2 CO, and NH 2 CHO has shed light on the interstellar chemistry of pre-biotic molecules and species carrying various biogenic elements (e.g., Saladino et al, 2006;Bisschop et al, 2007;Mendoza et al, 2014;López-Sepulcre et al, 2015;Allen et al, 2020;Jørgensen et al, 2020).…”
Section: The Organic Side Of the Galaxymentioning
confidence: 99%